2016
DOI: 10.1021/acsami.6b12502
|View full text |Cite
|
Sign up to set email alerts
|

Nb2O5 Nanostructure Evolution on Nb Surfaces via Low-Energy He+ Ion Irradiation

Abstract: We propose low-energy, broad-beam He ion irradiation as a novel processing technique for the generation of NbO surface nanostructures due to its relative simplicity and scalability in a commercial setting. Since there have been relatively few studies involving the interaction of high-fluence, low-energy He ion irradiation and Nb (or its oxidized states), this systematic study explores both effects of fluence and sample temperature during irradiation on resulting surface morphology. Detailed normal and cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
(128 reference statements)
0
11
0
Order By: Relevance
“…Apparently, the optical property was altered by the morphology change. Because the FN increases the optical absorbance significantly, the FN surface could be appropriate for solar-thermal application, [3] similar to W cases. [54] Here, the reflectance includes both the specular and diffuse reflectance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apparently, the optical property was altered by the morphology change. Because the FN increases the optical absorbance significantly, the FN surface could be appropriate for solar-thermal application, [3] similar to W cases. [54] Here, the reflectance includes both the specular and diffuse reflectance.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Pinholes were formed even at 1000 K; the size of pinholes was much smaller and protrusions were more prominent in Figure 1(a). [38] In previous studies, though protrusions were formed on Nb, no FNs were identified on the surface; [3,24] this would be because of the difference in the He flux and fluence. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 Different from W case, where grain orientation dependence with grain boundary was identified, [43] there were no clear grain boundary and grain orientation dependence.…”
Section: Morphology Changesmentioning
confidence: 95%
See 3 more Smart Citations